Fidelity of computational modelling of offshore jacket platforms. Issue 2 (6th June 2019) - Vilnay, Margi; Sivickij, Valdemaras; Watters, Frazer; Doerich-Stavridis, Cornelia; Chernin, Leon
Abstract : Fixed offshore jackets are the most commonly adopted rigs for exploration of offshore oil and gas resources. The present paper focuses on the modelling of a 4-legged X-braced jacket type platform using nonlinear finite element analysis. The nonlinear effects of joint flexibility, piled foundations and geometrical imperfections on the platform behaviour are investigated. Joint flexibility is modelled by introducing rigid or flexible joints into the jacket beam element model. A hybrid model, with the critically-loaded leg and connected joints built using shell elements, is applied for the investigation of localised effects on increasing joint flexibility. The soil-pile interaction is modelled using sets of decoupled springs distributed along the piles. The geometrical imperfections, generated based on the failure modes of the platform, are introduced in the compression legs of the jacket. The platform is loaded by operational and environmental loads. The environmental loads are gradually increased until platform failure occurs. The findings of the paper indicate that incorporation of joint flexibility and piled foundations result in the reduction of platform yielding and ultimate strength. The piled foundation affects platform stiffness severely. The imperfections increase platform deformability in the elastic rage and lead to dramatic reduction of jacket base shear capacity.